How Positive and Negative Childhood Experiences Interact With Resiliency Theory and the General Theory of Crime in Juvenile Probationers - Mueller, Kyle C. (Youth violence and juvenile justice, 2023)
Self-control and resiliency in juveniles are each thought to be relevant to the onset of delinquency and recidivism, and both are related to family environments and other childhood experiences. The general theory of crime is well established within the literature as an explanation for offending at all ages, and resiliency perspectives stress the importance of things like independence and morality to avoiding/desisting from deviance among juveniles. Here, Adverse Childhood Experiences (ACEs) and Positive Childhood Experiences (PCEs) are examined among 3604 juvenile probationers in the contexts of the general theory of crime and the compensatory, protective factor, and challenge models of resiliency theory. Results show that high ACE scores were associated with diminished self-control, and high PCE scores were correlated with better self-control. Policy implications are discussed.